Os efeitos provocados pela pandemia da Covid-19 nas estratégias de marketing das universidades comunitárias no Brasil - Silva, Wildenilson Sinhorini Vieira da (2022)
The COVID-19 pandemic is considered a health crisis of catastrophic proportions that, since 2020, has affected the whole of society. The impact caused by the infection caused by SARS-CoV-2 is not only restricted to the scope of health but also has consequences for the economy in the most different sectors, among them, higher education. In this study the purpose of this research was to answer the following problem: what are the effects caused by the COVID-19 pandemic on the strategies of community universities in Brazil? With this, we sought to map the marketing actions implemented to face the pandemic, identify university students' perceptions regarding the implemented actions, and compare the implemented actions and the students perceptions to understand the main marketing strategies adopted and the results obtained. For this research, a multi-method approach was used, with qualitative data collection, through 12 semi-structured in-depth interviews with marketing managers and quantitative, through an online questionnaire answered by 414 students from 7 Brazilian community universities. These research results contributed to the mapping of actions implemented by marketing managers in universities and serve to composse a possible protocol for the marketing departments of the HEI. In this way, the possibility of planning marketing strategies to mitigate the effects of future crises in the university sector is possible.